Clinical outcomes after multiple self-expandable metallic stent placement using stent-in-stent technique for malignant gastric outlet obstruction. Issue 21 (22nd May 2020) - Mo, Jin Won; Kim, Young Min; Kim, Jie-Hyun; Shin, Seung Yong; Youn, Young Hoon; Park, Hyojin
Abstract : Abstract: Self-expandable metallic stent (SEMS) placement is widely used for relieving symptoms in malignant gastric outlet obstruction (MGOO). This study aimed to evaluate the efficacy and safety of multiple gastroduodenal stent placement using the stent-in-stent technique and to identify factors predictive of stent patency. We retrospectively analyzed data from 170 patients with GOO receiving SEMS using the stent-in-stent technique between July 2006 and July 2018. Of these, 90 had been treated with SEMS placement for MGOO. Technical and clinical success rates were evaluated. Clinical outcomes and predictors of stent patency were also analyzed. Second SEMS placement was used in 34.4% of cases and 9.7% were treated with third SEMS placement because of prior stent dysfunction. Median stent patency time was 15.7 weeks for the first SEMS, 10.4 weeks for the second, and 11.3 weeks for the third. The technical and clinical success rates were 100% and 97.8% for the first SEMS, 100% and 90.3% for the second, respectively, and both 100% for the third. Multivariable analysis showed that use of covered SEMS and chemotherapy after first and second SEMS placement was significant predictors of stent patency. Serious complications such as bleeding or perforation did not occur in any patient. Second and third gastroduodenal SEMS placement using the stent-in-stent technique is safe and effective for management of first stent dysfunction in MGOO. Stent patency is significantly associated with the use of covered SEMS and chemotherapy after SEMS placement.